A multimodal optical approach for investigating 3D-printed carbon PEEK composites. (April 2022) - Pagliarulo, V.; Russo, P.; Leone, G.; D'Angelo, G.A.; Ferraro, P.
Highlights: 3D-printed carbon PEEK composite specimens with different orientations of the reinforcing fibres. Multimodal investigation approach focused on the synergy of different optical techniques. Low-cost manufacturing and characterisation procedures for aerospace and automotive. Abstract: In the industrial field, it is of great interest to identify fast and low-cost manufacturing procedures to guarantee reliable and functional products. In this frame, 3D printing is a fast and low-cost innovative technique and its capability to produce fibre-reinforced polymer matrix composites widely opens the application possibilities. 3D printing technology can form also composite materials made by short fibres that can be exploited for manufacturing parts and structures in high-tech sectors such as aerospace, automotive or naval, to cite some. Here we show how a multimodal approach can furnish a whole characterisation of reinforced composites produced with a 3D printing technology during and after tensile and flexural tests. In the multimodal strategy, we employed a couple of full-field and non-contact optical techniques, i.e. 2D-Digital-Image-Correlation (2D-DIC) and Electronic Speckle Pattern Interferometry (ESPI) in combination with SEM and optical microscope for analysing the sample at the micro and macroscale. The result of the work allows us to achieve a complete characterisation of the components realized by 3D printing.